Biophysical investigation of curcumin based nanocomposite for wound dressing application - Nagwa A. Kamel, Ahmed A. F. Soliman, Nehad N. Rozik, Salwa L. Abd-Elmessieh (Journal of Applied Pharmaceutical Science, 2018)
Curcumin (cur) loaded polyvinyl alcohol (PVA), chitosan (Cs) and PVA/Cs blend (50:50) were prepared with different concentrations of curcumin (0, 5, 10, and 15 wt%) using the solution casting technique and studied for wound dressing application. Physical characterization of the composites achieved through dielectric spectroscopy (DS), fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM) and transmission electron microscope (TEM). The wound dressing characteristics were evaluated by the water vapor transmission rate (WVTR), antimicrobial studies and cell viability assay. The scanning electron microscope revealed good dispersion of the nanocurcumin in the matrix. The dielectric properties of all composites were studied through the measurements of the permittivity ε′ and dielectric loss ε″. These results show that both values for PVA/cur nanocomposites greatly increase with increasing curcumin content which was found to be higher than those of the two individuals. On the opposite side, both ε′ and ε″ decrease with increasing curcumin content in case of Cs/cur and PVA/Cs/cur nanocomposites. The obtained electrical conductivity for all composites lies in the order of (10−9–10−14/S cm−1). WVTR of the samples decreased by increasing the curcumin %. Results of the cell viability assay confirmed that the addition of the curcumin has no toxic effect on the cells. PVA/cur nanocomposites displayed excellent antimicrobial activity.
Keywords: Dielectric,chitosan,polyvinylalcohol,nanocurcumin,nanocomposite,wound dressing.